Resilience of public administration bodies to cyberattacks - Szleszyński, Artur; Dudziak-Gajowiak, Dominika (Scientific Journal of the Military University of Land Forces, 2023)
Public administration bodies are responsible for the organization of crisis management in their allocated area of responsibility. Currently, the exchange of information between elements of crisis management is carried out using the telecommunications system. Thanks to the use of remote sensing, it is possible to exchange data, and build information about the crisis phenomenon on its basis. The responsibility for the protection of information resources is incumbent on heads of municipalities, mayors of cities or marshals of voivodeships (provinces) collecting and processing data in order to carry out the tasks of their subordinate offices. One of the elements of the crisis situation will be a cyberattack carried out against the IT infrastructure of the office in order to hinder or prevent it from performing its tasks. Such incidents have taken place in Poland. Of interest is the issue of managing an incident which directly affects a given office. The article presents an analysis of the cases of cyberattacks described in the media. The paper demonstrates passive reconnaissance methods used by cybercriminals.